Acupuncture Relieves Stress-Induced Depressive Behavior by Reducing Oxidative Stress and Neuroapoptosis in Rats - Cheng, Wen-Jing; Li, Peng; Huang, Wen-Ya; Huang, Yang; Chen, Wen-Jie; Chen, Yi-Ping; Shen, Jun-Liang; Chen, Jian-Kun; Long, Na-Sha; Meng, Xian-Jun (Frontiers in Behavioral Neuroscience, 2022)
Studies have shown that oxidative stress is closely related to the occurrence of depression. Acupuncture has proved to be an effective treatment for depression. In this study, the effect of acupuncture on oxidative stress and Nrf2 signaling pathway in the hippocampus of chronic unpredictable mild stress (CUMS) depression model rats were observed to further explore the mechanism of the antidepressant effect of acupuncture. Male SD rats were randomly divided into control group, CUMS group, acupuncture group, and fluoxetine group (n=10/group). Fluoxetine, a commonly used antidepressant, was used as a positive control drug in this research. The acupoints of Shangxing (DU23) and Fengfu (DU16) were selected, once every other day for 14 times in total. Rats in the fluoxetine group were given fluoxetine intragastrically once a day for 28 days. Behavioral experiments, Enzyme-linked immunosorbent assay (ELISA), western blot (WB), reverse transcription-polymerase chain reaction (RT-PCR), Nissl’s staining, and immunohistochemistry (IHC) were used to detect the effect of the intervention and the changes of factors related to oxidative stress, Nrf2 pathway, and neuronal apoptosis. The results showed that acupuncture and fluoxetine could increase the sugar preference rate and decrease immobility time in depression model rats. It also decreased significantly oxidative stress products such as ROS and H2O2, and elevated the protein and mRNA expressions of Nrf2 and HO-1. From Nissl’s staining, the treatment groups were more abundant nerve cells than model groups. Plus, acupuncture down-regulated the expression levels of Bax and caspase-3 and up-regulated the expression of Bcl-2. Our findings suggested that the acupuncture improved depression-like behavior of CUMS rats. And the CUMS-induced depression-like behaviors in rats were related to hippocampus oxidative stress and neuronal apoptosis. Therefore, acupuncture showed antidepressant effects via regulating the Nrf2 / HO-1 signaling pathway to reduce oxidative stress products, thus preventing neuronal apoptosis.